Pelaksanaan Putusan Peradilan Tata Usaha Negara (PTUN): Pengadilan tata usaha negara, Hukum, Indonesia, Putusan pengadilan - Leona Putri Sari; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2023)
Execution of the decision (executie) is the method and conditions that used by the tools of state power to help interested parties to carry out the judge's decision if the losing party is not willing to comply with the substance of the decision within the allotted time.limiting court decisions that have permanent legal force that are relevant to implementation, namely a decision that has been accepted by the parties or has not been submitted again legal action (appeal or cassation). Court decisions that have not yet obtained force the law still does not have the power of execution or in other words a court decision who still have legal remedies. State business as a manifestation of the implementation of the judicial function to control its course. The executive function in the form of testing a form of state administration decision issued by State Administrative Officials that the decision was in accordance with the provision legislation and general principles of proper government administration in accordance with Article 115 of Law Number 5 of 1986 concerning Administrative Court A state that states that only decisions have gained legal force fixed that can be implemented.